A Liberal Peace?: The Growth of Liberal Norms and the Decline of Interstate Violence. (April 2022) - Gill-Tiney, Patrick
How have understandings of fundamental norms of international society changed over time? How does this relate to the decline of interstate violence since 1945? Previous explanations have focused on regime type, domestic institutions, economic interdependence, relative power, and nuclear weapons, I argue that a crucial and underexplored part of the puzzle is the change in understanding of sovereignty over the same period. In this article, I propose a novel means of examining change in these norms between 1970 and 2014 by analyzing the content of UN Security Council resolutions. This analysis is then utilized in quantitative analysis of the level of violence dispute participants resorted to in all Militarized Interstate Disputes in the period. I find that as liberal understandings of fundamental norms have increased, that the average level of violence used has decreased. This points to a crucial missing component in the existing literature: that institutions can only constrain when political actors share the right norms.